PENGARUH CHALLENGE STRESSORS DAN ORGANIZATIONAL SUPPORT FOR CREATIVITY TERHADAP KREATIVITAS KARYAWAN YANG DIMEDIASI OLEH KETERLIBATAN KERJA (Fakultas Ekonomi Universitas Wisnuwardhana, 2022)
This study aims to analyze the mediating effect of Work Engagement on the effect of Challenge Stressor and Organizational Support for Creativity on Employee Creativity. This research was conducted quantitatively by using a questionnaire as a medium to collect data. The sample used in this study was online transportation drivers in several regions in Indonesia with a total of 105 samples. The distribution of the questionnaires was carried out by means of a survey via Google Form which was distributed through social media or directly to research respondents. The research data were analyzed using linear regression analysis using the SPSS version 25 program and testing the effect of Sobel mediation. The results showed that Challenge Stressor had a positive and significant effect on Work Engagement, Organizational Support for Creativity had a positive and significant effect on Work Engagement, Work Engagement had a positive and significant effect on Employee Creativity, and Challenge Stressor had a positive and significant effect on Employee Creativity. Organizational for Creativity does not have a positive and significant effect on Employee Creativity, and Work Engagement is proven to mediate the effect of Challenge Stressor and Organizational Support for Creativity on Employee Creativity.